2010
DOI: 10.1111/j.1469-8137.2010.03383.x
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus analysis of genetic divergence between outcrossing Arabidopsis species: evidence of genome‐wide admixture

Abstract: Summary• Outcrossing Arabidopsis species that diverged from their inbreeding relative Arabidopsis thaliana 5 million yr ago and display a biogeographical pattern of interspecific sympatry vs intraspecific allopatry provides an ideal model for studying impacts of gene introgression and polyploidization on species diversification.• Flow cytometry analyses detected ploidy polymorphisms of 2· and 4· in Arabidopsis lyrata ssp. kamchatica of Taiwan. Genomic divergence between species ⁄ subspecies was estimated based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 74 publications
1
27
0
Order By: Relevance
“…gemmifera (Japan) (cf. Wang et al, 2010). Young, healthy leaves were collected and dried in silica gel.…”
Section: Sampling and Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…gemmifera (Japan) (cf. Wang et al, 2010). Young, healthy leaves were collected and dried in silica gel.…”
Section: Sampling and Experimentsmentioning
confidence: 99%
“…Besides, multilocus analyses that assess the genetic divergence within and between sister species also provide genealogical information for inferring the phylogeography (Stadler et al, 2005;Wright and Gaut, 2005;Zhu et al, 2007;Zou et al, 2008;Wang et al, 2010). In addition to the bifurcate topologies that interest the evolutionists, molecular dating provides much useful information (Wikstrom et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It is distributed throughout the amphiBeringian region but is also found in Japan, Korea, and Taiwan. There is also evidence of past gene flow in Europe between diploid A. lyrata and A. halleri on the basis of either nuclear genes (13) or self incompatibility alleles (14).…”
mentioning
confidence: 99%
“…In this study, genetic analyses of all markers revealed non-stop gene flow between species in this genus, a pattern contradicting with the "isolation" model. It has been known that gene flow between closely related species is not rare in plants (Wang et al 2010). Besides, STRUCTURE analyses of microsatellite loci also revealed that genetic composition of some populations was mixed with alleles from other species, although with little extent, again likely indicating non-stop interspecific introgression (Fig.…”
Section: Species Divergence and Genetic Differentiation In Fatsiamentioning
confidence: 96%